Selection of maize genotypes resistant to pink stem borer and sugarcane borer - Ngwuta, A.; Ajala, S.; Obi, I.U.; Ene-Obong, E.E. (David Publishing Company, 2015)
Maize is an important economic crop grown in Nigeria. Its production is dramatically affect by the pink stem borer—Sesamia calamistis (Hampson, Noctuidae) and sugarcane borer—Eldana saccharina (Walker, Pyralidae) that are endemic in Southeastern Nigeria. In areas of stress, existing genotypes may marginally do well due to their inherent capabilities. Therefore, it is possible to find useful genes in such areas of stress, since such genes have been responsible for the survival of host crops over the years. Evaluation study was conducted for a range of agronomic characteristics and resistance attributes for 209 local maize collections from Southeastern Nigeria along with three improved check varieties. Field trials were conducted at three locations in a total of four environments in 2001. Highly significant genotypic variances as were noted in all the traits, are indicative of the magnitude of variation that exists among the genotypes, thus providing the opportunity of selection for desirable traits. Furthermore, four traits, namely, leaf feeding, ear damage, stalk lodging and yield were used from across the environments to construct a rank summation index (RSI), which was used to rank the entries for resistance to stem borers. This RSI led to the identification of 11genotypes which represents the best 5% of the 212 genotypes in resistance ability. Genotype AMA TZBR-WC1 (from International Institute of Tropical Agriculture (IITA), Ibadan) had the best overall resistance levels, followed by genotypes SE NG-77 and SE NG-67 (from Umuahia North), SE NG-62 (from Ikwuano), SE NG-148 (from Ukwa West), SE NG-106 (from Bende), SE NG-119 (from Isiala Ngwa), SE NG-33 (from Ikwuano) and SE NG-65 (from Umuahia North).